Antroponimy w hejcie - Naruszewicz-Duchlińska, Alina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
Hate refers to online posts aimed at depreciating someone or something by expressing a provocative negative opinion about them. This article discusses the function and place of anthroponyms in such posts. Its goal is to present the observations and conclusions concerning the role of anthroponyms and their usage by haters. The study material was collected from Facebook, Twitter and wm.pl and subjected to qualitative analysis.